PISA XALQARO BAHOLASH TADQIQOTIDA KOMPETENSIYALARNI BAHOLASH MASALASI - Turmanov, Q.A. (SCIENCE and SOCIETY, 2022)
The article discusses the main directions of the PISA international assessment program, its objectives, key skills, contexts and competencies. Recommendations were also given on preparing for the international PISA assessment program and building students’ knowledge, skills and competencies.